Using Mininet for emulation and prototyping Software-Defined Networks - De Oliveira, Rogerio Leao Santos; Schweitzer, Christiane Marie [UNESP]; Shinoda, Ailton Akira [UNESP]; Prete, Ligia Rodrigues (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Software-Defined Networks (SDNs) represents an innovative approach in the area of computer networks, since they propose a new model to control forwarding and routing data packets that navigate the World Wide Web. Since research on this topic is still in progress, there are not many devices such as routers and switches that implement SDN functionalities; moreover, the existing ones are very expensive. Thus, in order to make researchers able to do experiments and to test novel features of this new paradigm in practice at a low financial cost, one solution is to use virtual network emulators. As a result, this paper focuses on study and evaluation of SDN emulation tool called Mininet. Initial tests suggested that the capacity of rapid and simplified prototyping, the ensuring applicability, the possibility of sharing results and tools at zero cost are positive factors that help scientists boost their researches despite the limitations of the tool in relation to the performance fidelity between the simulated and the real environment. After presenting some concepts of this paradigm, the purpose of its appearance, its elements and how it works, some net prototypes are created to better understand the Mininet tool and an evaluation is done to demonstrate its advantages and disadvantages. © 2014 IEEE.
Keywords: emulation; Floodlight; Mininet; OpenFlow; Software Defined Networking; virtualization